THE EFFECT OF MERIT-BASED CAREER DEVELOPMENT ON PROFESSIONALISM AND PERFORMANCE OF CIVIL SERVANTS IN INDONESIAN PORT ADMINISTRATION - Zakariyah Ardhi Nugroho; Rifda Fitrianty; Sri Rahayu (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the effect of merit-based career development on professionalism and performance of civil servants at the Office of Harbormaster and Port Authority Class III Tanjung Pakis, Indonesia. Using a quantitative associative approach with survey methodology, data were collected from sixty-five civil servants through saturated sampling with structured questionnaires, and direct observation. The research variables consisted of merit-based career development as the independent variable measured through competence, qualification, promotion, performance assessment, and career transparency indicators, and two dependent variables: professionalism measured through work discipline, integrity, responsibility, loyalty, and work ability, and performance measured through work quality, quantity, timeliness, effectiveness, and cooperation. Data analysis employed SmartPLS 4 encompassing validity and reliability testing, classical assumption tests, multiple linear regression, partial t-tests, simultaneous F-tests, and coefficient of determination analysis. The results indicate that merit-based career development exerts a statistically significant positive effect on both professionalism and performance of civil servants in the maritime technical administration context. The findings demonstrate that transparent and competency-based advancement mechanisms create integrated motivational conditions that simultaneously enhance professional identity and drive productive behaviors in safety-critical port operations. This study extends merit system research into an underexplored specialized government agency setting and provides evidence-based guidance for strengthening human resource management practices in Indonesia's maritime governance sector.